War and Diplomacy in Modern Japan - Hattori, Ryuji. author. (orcid)0000-0002-5003-9582 Link aut Link
XVII, 189 p. 1 illus.
Keywords: This open access book examines the life and work of Koki Hirota, who served as Japan's foreign minister and prime minister from 1933 to 1938 - the period that saw the final Japanese diplomatic attempts at achieving a modus vivendi with China before the outbreak of the Second Sino-Japanese War. It looks at the failed attempts to prevent that war from evolving into a protracted conflict. Hirota's actions and inactions during this time resulted in a death sentence at the Tokyo Trials following the end of the Second World War, making him the only civilian official to meet such a fate. Hirota is seen as a martyr-like figure in Japan, but this book counters this public image by showing how, despite initially championing a cooperative relationship with China as foreign and prime minister, he continually acquiesced to the military's demands before being swept away by the rise of populist politics that followed early Japanese success in the Second Sino-Japanese War. As the first biography of Hirota to be published in English, this book provides an in-depth account of Sino-Japanese relations and Japanese diplomacy during this critical period and examines the ultimate failure of the civilian government to check the adventurism of the Japanese army. It is relevant to historians of Japan, and to those interested in diplomatic history, and the Second World War - as well as scholars working in various areas of contemporary East Asian politics.